Determinants of Job Satisfaction of Public Sector Organizations’ Employees in Six Continents: A Systematic Review - Zainal Putra; Jasman J. Ma’ruf; Mukhlis Yunus; Hamdi Harmen; Hanudin Amin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to systematically review the empirical literature on the determinants of employees’ job satisfaction in public sector organizations worldwide. This study conducted a systematic review following the protocol proposed by Lee and Cummings. Data sources utilize electronic databases, such as Scopus, PubMed, and Google Scholar, which were searched from 2008 to February 2022. The review method involves analyzing articles that examine the factors influencing employee job satisfaction in public sector organizations. Team members independently reviewed and determined each paper that met the inclusion criteria. Then we assessed the quality of the articles using a predetermined quality assessment instrument. Next, we perform data extraction. Finally, we conducted a comprehensive content analysis to categorize the factors related to employee job satisfaction. The results concluded that implementing appropriate leadership styles, prosocial behavior, rewards, organizational commitment, organizational justice, empowerment, emotional intelligence, and organizational communication can increase job satisfaction in public sector organizations. Toxic leadership style and job stress can reduce employee job satisfaction. Besides, we also revealed some inconsistencies in research results, which have provided research gaps for other researchers to follow up on in the future.